Don't just sit there : transitioning to a standing and dynamic workstation for whole-body health - Bowman, Katy (Propriometrics Press, 2015)
If sitting is indeed the new smoking, then certainly we should quit. But is sitting really the problem, or is something else going on? Is getting better as simple as kicking over your chair and standing all day in front of the same computer, under the same fluorescent lighting or is there something more to be learned from the data about how people work best? Don't Just Sit There explains why swapping one static position for another isn't taking a big enough look at the problem, and provides corrective exercise and lifestyle solutions to help you safely and effectively transition away from the conventional office set-upallowing you to reap the enormous benefits of moving more throughout the day while getting your work done.